A Sociolinguistic Analysis of Taboo Words in Deadpool 2 - Salsabila Rahmania; Aris Munandar (Universitas Gadjah Mada, 2021)
The purpose of this research is to describe the types and functions of taboo words uttered by the characters, and describe the social background that affect the main character’s utterances in Deadpool 2. The data are utterances containing taboo words. The analysis focuses on the types and functions of taboo words by applying Azzaro’s (2005) theory. The finding shows, 1) there are five types of taboo words in use. The most frequently used taboo is Sexual term with 70 occurrences (52.2%), followed by physical term with 23 occurrences (17.2%), religious term with 21 occurrences (15.7%), scatological term with 17 occurrences (12.7%), and mental term with 3 occurrences (2.2%). 2) There are two functions of taboo words: swearing with 82 occurrences (64%), and insult with 46 occurrences (36%). 3) There are two social variables that affect the main character’s use of taboo words: occupational hierarchy and social status.